The impact of interfaces on the performance of organic photovoltaic cells - Steim, Roland (KIT Scientific Publishing, 2010)
Organic photovoltaic is an attractive technology to solve future energy supply scenarios. To further increase the potential of this technology novel absorber materials and interface materials have to be developed. In this work the paramount importance of interface materials for efficient as well as stable organic photovoltaic cells and modules is demonstrated. The general requirements of interface materials are elaborated and properties of a novel interface material which meets the demands are investigated experimentally and by simulations.